Economic costs of hospitalized diarrheal disease in Bangladesh: a societal perspective - Abdur Razzaque Sarker; Marufa Sultana; Rashidul Alam Mahumud; Nausad Ali; Tanvir M Huda; M. Salim uzzaman; Sabbir Haider; Hafizur Rahman; Ziaul Islam; Jahangir A. M. Khan; Robert Van Der Meer; Alec Morton (BMC, 2018)
Abstract Background Diarrheal diseases are a major threat to human health and still represent a leading cause of morbidity and mortality worldwide. Although the burden of the diarrheal diseases is much lower in developed countries, it is a significant public health problem in low and middle-income countries like Bangladesh. Though diarrhea is preventable and managed with low-cost interventions, it is still the leading cause of morbidity according to the patient who sought care from public hospitals in Bangladesh indicating that significant resources are consumed in treating those patients. The aim of the study is to capture the inpatients and outpatient treatment cost of diarrheal disease and to measure the cost burden and coping mechanisms associated with diarrheal illness. Methods This study was conducted in six randomly selected district hospitals from six divisions (larger administrative units) in Bangladesh. The study was performed from the societal perspective which means all types of costs were identified, measured and valued no matter who incurred them. Cost analysis was estimated using the guideline proposed by the World Health Organization for estimating the economic burden of diarrheal diseases. The study adopted quantitative techniques to collect the household and hospital level data including structured and semi-structured questionnaires, observation checklists, analysis of hospital database, telephone interviews and compilation of service statistics. Results The average total societal cost of illness per episode was BDT 5274.02 (US $ 67.18) whereas the average inpatient and outpatient costs were BDT 8675.09 (US $ 110.51) and BDT 1853.96 (US $ 23.62) respectively. The cost burden was significantly highest for poorest households, 21.45% of household income, compared to 4.21% of the richest quintile. Conclusions Diarrheal diseases continue to be an overwhelming problem in Bangladesh. The economic impact of any public health interventions (either preventive or promotive) that can reduce the prevalence of diarrheal diseases can be estimated from the data generated from this study.